Use of species delimitation approaches to assess biodiversity in freshwater planaria (Platyhelminthes, Tricladida) from desert springs. Issue 2 (22nd January 2020) - Inoue, Kentaro; Pohl, Alexa L.; Sei, Makiri; Lang, Brian K.; Berg, David J.
Abstract: Chihuahuan Desert springs in New Mexico and Texas harbour many endemic aquatic species. Often, these taxa share similar phenotypic characters, making it difficult to assess biodiversity accurately. Even though free‐living planaria (Platyhelminthes, Tricladida) occur in high densities, they are often omitted from biodiversity assessments of freshwater habitats owing to a lack of expertise in identifying them and lack of concern for conservation of these poorly known organisms. Using phylogenetic and species delimitation approaches, the diversity of planaria was examined from 12 springs in the northern Chihuahuan Desert. Mitochondrial and nuclear DNA sequences were used to reconstruct a phylogeny and then to delineate putative species from these springs via genetic distance and multispecies coalescent methods. The results showed that the planaria in the northern Chihuahuan Desert probably belong to four putative species; three of these are locally endemic, and the other is widely distributed across the region. These putative species may have experienced different evolutionary histories primarily because the locally endemic taxa have limited dispersal capabilities. The results suggest the need for morphological examination in order to allow the description of these putative species. This study not only uses DNA barcoding to estimate accurately the total diversity of freshwater planaria before conventional species identification, but also identifies hidden biodiversity in springs of the northern Chihuahuan Desert. These ecosystems require aggressive conservation action to protect vulnerable habitats that contain a wealth of endemic species.